Circular business activities and economic performance optimization in EU countries: towards consumption footprint management - Olugbenga Michael Adewumi; Chukwuemeka Echebiri; Andrew Adewale Alola (Cogent Economics & Finance, 2024)
As circular business activity is a pivotal component of the European Green Deal, this study examines its impact on economic prosperity by examining how the model influences income levels. The investigation spans a panel of 27 European Union (EU) member countries from 2014 to 2023, factoring in the income effect of consumption footprint and public trust in governing institutions. Based on the system Generalized Method of Moments (GMM) estimators of the dynamic panel model, the results reveal that circular business activities enhance economic well-being. However, the interaction effect of consumption footprint limits the full potential of this enhancing effect. Moreover, as public confidence in government institutions improves, so does economic well-being. This perspective underscores the pivotal role of trust in bolstering the economic benefits of circular business activities, leading to more robust societal conditions. Overall, the study suggests that while circular business activities can improve economic well-being, efficient management of the consumption footprint is crucial for optimization. Its policy implication emphasizes balancing economic aspects with social, institutional, and environmental elements to enhance individual well-being. Thus, the findings contribute to the literature and provide valuable policy insights into circular economy models, opening up avenues for future consideration. This study highlights the significant role of circular business activities in enhancing economic prosperity within the framework of the European Green Deal. By analyzing data from 27 EU member countries between 2014 and 2023, the research demonstrates that while circular business practices positively impact economic well-being, their full potential is constrained by the interaction effect of consumption footprint. Additionally, it finds that increased public trust in government institutions further amplifies the economic benefits of circular activities. The study underscores the importance of managing consumption footprints and fostering institutional trust to optimize circular economy models' economic and societal advantages. These insights offer valuable policy implications, emphasizing the need to integrate various factors to improve overall well-being.
Keywords: 330; Circular economy; economicwell-being optimization; public confidence; consumption footprint; EU